Mediation Procedure in Religious Courts in Indonesia in the Perspective of Thought Wahbah Al-Zuhaily - Suhastra, Pahruroji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Marriage is expected to be harmonious and happy. However, there are still many domestic disputes that end in divorce. Divorce cases in Indonesia are still very high. Divorce has many negative effects. Efforts to maintain the integrity of the household is necessary. One of them is mediation. This study aims to find out how the mediation procedure at the Religious Courts in Indonesia is in the perspective of Wahbah Al-Zuhaily's thought? Research conducted by the author using a type of library research (Library Research). While the approach is descriptive analysis; in this case describing and explaining conceptual phenomena. Literature study with main sources At-Tafsir al-Munir fi al-qidah wa al-Syari'at wa al-Manhaj and al-Fiqh al-Islamy Wa Adillatuhu by Wahbah al-Zuhaily and Supreme Court Regulation No. 1 of 2016 governing procedures mediation in court. From the research that has been conducted by researchers, it can be concluded that there are some similarities between the mediation procedures that apply to the Religious Courts in Indonesia and Wahbah al-Zuhaily's views in terms of the importance of mediation in efforts to reconcile disputes and disputes that occur between husband and wife. Likewise, in the main principles of mediation, mediation procedures at the Religious Courts in Indonesia are in line with Wahbah al-Zuhaily's thoughts. As in the qualifications of the judge or mediator and the limits of his authority in conducting mediation. Hopefully this research will bring benefits both theoretically and practically to all interested parties.